Women in tech entrepreneurship research - literature review - Fadhilah Fadhilah; Fandya Rasmita Diniswara; Mareta Putri Hasyatamma; Nafisa Nurfadila (President University, 2022)
In this era, women have become important players in the field of business and entrepreneurship. Technology provides opportunities for women to expand their social networks by creating new opportunities for businesses where entrepreneurial barriers can be overcome by adopting technology, particularly in developing countries. The more research and publication on women entrepreneurship with 24 journal selected from 68 journal available, this makes researchers feel the need to study to find out how and the extent of the development of women entrepreneurs in the field of technology. The data collection in this study was taken from Scopus web by entering the keywords that the author used to get the desired amount of publication and information. This study uses bibliometric analysis method conducted using co-authorship and co-citation analysis with the help of VOSviewer software. This study will also mention which developing countries have published and researched on this topic as well as the extent of relationships between authors in each existing journal.